Relationship between Exercise with Blood Pressure Stability among Hypertension Elderly - Dion Kunto Adi Patria; Novila Eka; Maulana Maulana (Genius Journal, 2023)
Objective: This study aims to determine the relationship between elderly gymnastics and blood pressure stability in elderly hypertension in Porpri Posyandu Lansia Bunulrejo. Methods: This research is correlated with a cross-sectional approach. Samples were chosen by using the purposive sampling technique with inclusion and exclusion criteria, which got 25 people. The variables measured in this study were the elderly gymnastic relationship and blood pressure stability. The test statistic used was spearman rank correlation with a 95% confidence level. Results: The results of bivariate analysis showed that there was a significant correlation between daily gymnastics and stabilizing blood pressure (p = 0,000), with a correlation strength of 0,710. Conclusion: From the research results, it can be concluded that there is a relationship between elderly gymnastics and blood pressure stability in people with hypertension.